Omalizumab for Chinese patients with moderate-to-severe allergic asthma in real-world clinical setting: a prospective, observational study - Wen Wang; Yue Guo; Jieying Li; Congying Zou; Lifang Zhao; Ya Zhu; Feiran Wang (BMJ Open Respiratory Research)
Background We aimed to investigate the effectiveness of omalizumab, a monoclonal anti-immunoglobulin E antibody, in Chinese patients with moderate-to-severe allergic asthma in real-world clinical practice.Methods This single-centre, prospective, observational study included Chinese patients aged 14–75 years with moderate-to-severe allergic asthma according to the Global Initiative for Asthma criteria. Omalizumab was administered subcutaneously, and the investigator collected real-world data on exacerbations, steroid exposure, pulmonary function and laboratory assessments at weeks 16, 24, 52, 104 and 156 after treatment initiation. The primary outcome was reduced exacerbations, measured as the proportion of patients with exacerbations in the year following omalizumab initiation. Bowker’s test for paired proportions was performed to compare exacerbation rates before and after treatment initiation. A generalised linear mixed model was used to compare the number of exacerbations.Results The mean treatment duration was 46.6 weeks for the full analysis set (n=398). The proportion of patients with exacerbations in the year before and after omalizumab initiation was 80.4% (181/225) and 18.7% (42/225) (difference: −61.8%, 95% CI −68.5 to –54.0, p<0.0001), respectively. At week 52, 67.4% of patients discontinued oral corticosteroids, and 19.5% reduced inhaled corticosteroids. The Asthma Control Test scores increased by 4.6 at week 52 from baseline (p<0.001). Forced expiratory volume in 1 s increased by 11.2% and 9.0% at weeks 24 and 52, respectively, from baseline (p<0.01). Injection site reactions (5.2%) were the most frequently reported adverse event.Conclusions In real-world clinical practice, omalizumab treatment remarkably reduced exacerbations in Chinese patients with moderate-to-severe asthma. Omalizumab reduced the use of oral corticosteroids and improved asthma control and pulmonary function.